No Association Found Between Traditional Healer Use and Delayed Antiretroviral Initiation in Rural Uganda - Horwitz, Russell H.; Tsai, Alexander C.; Maling, Samuel; Bajunirwe, Francis; Haberer, Jessica E.; Emenyonu, Nneka; Muzoora, Conrad; Hunt, Peter W.; Martin, Jeffrey N.; Bangsberg, David R. (AIDS and Behavior, 2013)
Traditional healer and/or spiritual counselor (TH/SC) use has been associated with delays in HIV testing. We examined HIV-infected individuals in southwestern Uganda to test the hypothesis that TH/SC use was also associated with lower CD4 counts at antiretroviral therapy (ART) initiation. Approximately 450 individuals initiating ART through an HIV/AIDS clinic at the Mbarara University of Science and Technology (MUST) were recruited to participate. Patients were predominantly female, ranged in age from 18 to 75, and had a median CD4 count of 130. TH/SC use was not associated with lower CD4 cell count, but age and quality-of-life physical health summary score were associated with CD4 cell count at initiation while asset index was negatively associated with CD4 count at ART initiation. These findings suggest that TH/SC use does not delay initiation of ART
Keywords: HIV/AIDS; Traditional healer; Spiritual counselor; Late presentation; Uganda